Indications for partial parotidectomy using retrograde dissection of the marginal mandibular branch of the facial nerve for benign tumours of the parotid gland. Issue 8 (October 2018) - Suzuki, K.; Iwai, H.; Yagi, M.; Fujisawa, T.; Kanda, A.; Konishi, M.; Kobayashi, Y.; Tomoda, K.; Yamashita, T.
Abstract: The aims of this study were to evaluate the efficacy of partial parotidectomy using retrograde dissection of the marginal mandibular branch of the facial nerve for benign tumours of the parotid gland and to establish the indications for its use. We examined 106 consecutive patients with previously untreated benign tumours in the lower portion of the parotid gland who were treated by parotidectomy. The first group (anterograde group, n=52) consisted of those who had standard anterograde parotidectomy. The remaining patients, who underwent retrograde parotidectomy, were further divided into two groups: those in whom the upper edge of the tumour was located below the mastoid tip (below mastoid group, n=46) or those in whom it was above the mastoid tip (above mastoid group, n=8). The operating time was significantly shorter in the below mastoid group (141.2, 127.5, and 98.1 minutes, respectively) as was intraoperative blood loss (41.1, 53.0, and 24.4 ml, respectively), compared with the other two groups. There was a higher incidence of facial nerve dysfunction in the above mastoid group postoperatively (4/8) than in the other two groups. The results suggested that the presence of a tumour of any size located below the mastoid tip is a good indication for parotidectomy using retrograde dissection of the marginal mandibular branch of the facial nerve.